2021
DOI: 10.1002/pc.26181
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the nondestructive performance evaluation of fiber‐reinforced polymer composite laminate immersed in produced water using embedded fiber Bragg grating sensor

Abstract: Fiber-reinforced polymer (FRP) composites are exposed to various corrosive media during their service life, which adversely affects their material properties. Here, a novel approach is developed to investigate the long-term performance of glass FRP composite laminate immersed in produced water generated in oil fields. This is achieved by monitoring the internal hygroscopic strain developed over the aging time using embedded fiber Bragg grating sensor. Composite material strength reduction over the immersion ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…There are many types of FOS, fiber Bragg gratings (FBG), being one of them, have found extensive use in literature for strain monitoring and are therefore selected for the present research. Recently, embedded FBG sensors have shown the capability to measure strain developed by hygroscopic aging, [38] environmental effects on strain can therefore also be monitored. Regarding SHM, studies found in literature [39,40] can be used for validating the results.…”
Section: Non-destructive Techniquesmentioning
confidence: 99%
“…There are many types of FOS, fiber Bragg gratings (FBG), being one of them, have found extensive use in literature for strain monitoring and are therefore selected for the present research. Recently, embedded FBG sensors have shown the capability to measure strain developed by hygroscopic aging, [38] environmental effects on strain can therefore also be monitored. Regarding SHM, studies found in literature [39,40] can be used for validating the results.…”
Section: Non-destructive Techniquesmentioning
confidence: 99%
“…Fiber Bragg Grating (FBG) sensors, known for their small size and weight, immunity to electromagnetic interference, and resistance to corrosion, 2,3 are one of the preferred sensors used in smart composites. [4][5][6][7][8][9][10] Figure 1 presents one instance of the potential application of smart composites embedded with FBG sensors used in the intelligent wing skin, which enables online monitoring of deformation and damage. 11 In addition, FBG sensors are also increasingly applied in the space domain.…”
Section: Introductionmentioning
confidence: 99%
“…With the application of these smart composites, real‐time monitoring of the health state of aircraft can be achieved, leading to its enhanced safety and reliability. Fiber Bragg Grating (FBG) sensors, known for their small size and weight, immunity to electromagnetic interference, and resistance to corrosion, 2,3 are one of the preferred sensors used in smart composites 4–10 . Figure 1 presents one instance of the potential application of smart composites embedded with FBG sensors used in the intelligent wing skin, which enables online monitoring of deformation and damage 11 …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in another study, FBG sensors monitor the health of a composite structure bonded on the metallic substrate. [ 20 ] Mohanta et al [ 21 ] used an embedded FBG sensor to monitor the long‐term degradation of epoxy–glass composite in corrosive water. It is found that the long‐term stability can be effectively monitored by tracking the hygrothermal strain developed on the specimens immersed in corrosive produced waters.…”
Section: Introductionmentioning
confidence: 99%